Effectiveness of Snakehead Fish Extract (Channa starata) on Perineal Wounds - Triana Indrayani; Andi Julia Riviana (Health and Technology Journal (HTechJ), 2023)
Injuries to the birth canal can occur accidentally, such as in an episiotomy. Of 85% of maternity mothers who experienced injuries, 35% experienced perineal rupture, 25% experienced cervical rupture, 22% experienced vaginal injuries, and 3% experienced urethral rupture. This study aimed to determine the effectiveness of snakehead fish extract on the healing of perineal wounds in maternity mothers at the Z Clinic, Tangerang. This study is experimental research with a quasi-experimental research design with a non-equivalent control group design. The sample in this study was maternity mothers. Data in this study were analyzed using Univariate and bivariate analyses (Mann-Whitney test). It was found that the average healing of perineal wounds in the group given snakehead fish extract on day 3 was 9.2, while the average healing of perineal wounds on day 8 was 6.1. Then the average healing of perineal wounds in the group not given snakehead fish extract on day 3 was 9.2, while the average healing of perineal wounds on day 8 was 7.0. There is an effect of snakehead fish extract on the healing of perineal wounds in maternity mothers at the Z clinic, Tangerang with a p-value = 0.001. There is an effect of snakehead fish extract on the healing of perineal wounds in maternity mothers.